2015
DOI: 10.4161/15384101.2014.977096
|View full text |Cite
|
Sign up to set email alerts
|

The synergistic inhibition of breast cancer proliferation by combined treatment with 4EGI-1 and MK2206

Abstract: Abbreviations: eIF4E, eukaryotic translation initiation factor 4E; 4EBP1, eIF4E-binding protein 1; p70S6K, ribosomal p70 S6 kinase; mTORC1, mammalian target of rapamycin complex 1; mTORC2 mammalian target of rapamycin complex 2; PI3K, phosphatidylinositol 3-kinase; ER stress, endoplasmic reticulum stress.Cap-dependent translation is a potential cancer-related target (oncotarget) due to its critical role in cancer initiation and progression. 4EGI-1, an inhibitor of eIF4E/eIF4G interaction, was discovered by scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…MK-2206 has an antiproliferative effect on a range of solid tumors (Molife et al, 2014). Additionally, consistent with current research, in vivo dose-response curves showed that inhibition of AKT signaling with the inhibitor MK-2206 could attenuate cell growth (Wang et al, 2015;Wu et al, 2019;Zhao et al, 2014), the xenograft tumor of the MTDH knockdown with PTX + MK2206 treatment group was the smallest compared with the other groups in the in vivo experiments. Taken together, our results suggest that MTDH knockdown combined with MK-2206 enhances the effects of chemosensitivity to PTX by inhibiting the activation of the AKT/GSK3β pathway in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…MK-2206 has an antiproliferative effect on a range of solid tumors (Molife et al, 2014). Additionally, consistent with current research, in vivo dose-response curves showed that inhibition of AKT signaling with the inhibitor MK-2206 could attenuate cell growth (Wang et al, 2015;Wu et al, 2019;Zhao et al, 2014), the xenograft tumor of the MTDH knockdown with PTX + MK2206 treatment group was the smallest compared with the other groups in the in vivo experiments. Taken together, our results suggest that MTDH knockdown combined with MK-2206 enhances the effects of chemosensitivity to PTX by inhibiting the activation of the AKT/GSK3β pathway in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 85%
“…Our results also suggest that direct targeting of capdependent translation with 4EGI-1 abrogates the ability of HPIP to promote gastric tumor growth in vivo, indicating that targeting the eIF4F complex may provide a promising treatment strategy for GC patients with elevated HPIP expression. Indeed, several translation initiation inhibitors, including eIF4E-specific antisense oligonucleotides (ASOs) and silvestrol that suppresses cap-dependent translation by inhibiting the activity of eIF4A, have recently exerted effective antitumor effects with limited toxicity in mice (23)(24)(25)(26). In addition, targeting mTORC1 presents an alternative strategy for blocking cap-dependent translation.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the mechanisms that underlay this effect, we examined different branches of the mTOR pathway. We found that the small molecule 4EGI-1, which inhibits mTORC1 signaling and cap-dependent translation initiation (by binding to eIF4E and disrupting the eIF4E/eIF4G association) [54, 68], induces antibiotic-mediated readthrough. As CRC cells that responded to mTOR inhibition by increased PTC readthrough show high levels of 4EPB-1 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Other compounds such as the small molecules CDX5-1 [21] or the drug mefloquine [75], that do not induce readthrough when used as single agents, enhance AAG-mediated readthrough activity, possibly by targeting the translation machinery in a still unclear mechanism. It is also possible that the ability of 4EGI-1 to potentiate PTC readthrough stems from its inhibitory effect on mTORC1 signaling, which may be independent of its role in cap-dependent translation initiation [68]. As AAGs induce readthrough by reducing ribosomal proofreading during translation, a combination with agents that affect translation may lead to the development of improved readthrough-inducing compounds.…”
Section: Discussionmentioning
confidence: 99%